AL-AFÊ»Ä€L AL-INJÄ€ZIYYAH AT-TAUJÄªHIYYAH DALAM NOVEL SYAIÊ»UN FÄª SHADRÄª KARYA ICHSÄ€N ABDU AL-QUDDÅªS: KAJIAN PRAGMATIK - Jawat Nur, Abdul (Arabic Letters and Department, 2017)
This paper will describe al-afÊ»Äl al-injÄziyyah at-taujÄ«hiyyah or acts of directive illocution speech in the novel SyaiÊ»un fÄ« ShadrÄ« the work of IchsÄn 'Abdu Al -QuddÅ«s which is studied based on pragmatic studies. Novel SyaiÊ»un fÄ« ShadrÄ« is a novel classified as new (2016) in which many expressions containing acts of directive illocution speech. This is the reason for this research. To facilitate the course of research, this research through three strategic stages, namely data collection methods, data analysis methods, and methods of reporting the results of data analysis. Based on research that has been done concluded that in the novel SFS IchsÄnby'Abdu Al-QuddÅ«s is used various kinds of the act of directive illocution speech. They are (1) The act of saying thalabiyyah is a request to do or leave something, such as: rule 'amr', ask permission 'isti'zÄn ', suggests' iqtirÄch', warns' tachdzÄ«r ', motivates' tasyjÄ«' ', begs attention' tanbÄ«h, threatens' tahdÄ«d', prays'du'Ä', swearing 'qasam' and (2) The act of nafsiyyah speech is a speech act related to psychological conditions, such as motivating, cursing, pitting, and joking.